English teacher empowerment: The contribution of professionalism and work ethic in a non-formal education - Somariah Fitriani; Hery Muljono (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2023)
Since empowerment significantly contributes to the development of organizations and individuals, including schools and teachers, the issues of empowerment have drawn a lot of attention from all different types of organizations. Thus, the study set out to investigate the effects of professionalism and teacher empowerment on the work ethic of those who teach in non-formal education. This survey's cross-sectional study methodology was used, and the respondents were non-formal teachers who were employed as permanent English teachers in English language institutions. In this study, a causal survey method and a path analysis technique were both employed. The study indicated that professionalism and empowerment both considerably affect work ethics, and professionalism greatly affects empowerment. It also showed how professionalism has a substantial indirect impact on empowerment in terms of work ethic.